Ageing in a collective: the impact of ageing individuals on social network structure. (10th April 2023) - Siracusa, Erin R.; Pereira, André S.; Brask, Josefine Bohr; Negron-Del Valle, Josué E.; Phillips, Daniel; ,; Platt, Michael L.; Higham, James P.; Snyder-Mackler, Noah; Brent, Lauren J. N.
Abstract : Ageing affects many phenotypic traits, but its consequences for social behaviour have only recently become apparent. Social networks emerge from associations between individuals. The changes in sociality that occur as individuals get older are thus likely to impact network structure, yet this remains unstudied. Here we use empirical data from free-ranging rhesus macaques and an agent-based model to test how age-based changes in social behaviour feed up to influence: (i) an individual's level of indirect connectedness in their network and (ii) overall patterns of network structure. Our empirical analyses revealed that female macaques became less indirectly connected as they aged for some, but not for all network measures examined. This suggests that indirect connectivity is affected by ageing, and that ageing animals can remain well integrated in some social contexts. Surprisingly, we did not find evidence for a relationship between age distribution and the structure of female macaque networks. We used an agent-based model to gain further understanding of the link between age-based differences in sociality and global network structure, and under which circumstances global effects may be detectable. Overall, our results suggest a potentially important and underappreciated role of age in the structure and function of animal collectives, which warrants further investigation. This article is part of a discussion meeting issue 'Collective behaviour through time'.